Edge advances in nanodrug therapies for osteoarthritis treatment - Liao, Jinfeng; Gu, Qingjia; Liu, Zheng; Wang, Hailian; Yang, Xian; Yan, Rongkai; Zhang, Xiaofeng; Song, Siyuan; Wen, Lebin; Wang, Yi (Frontiers in Pharmacology, 2024)
As global population and lifestyles change, osteoarthritis (OA) is becoming a major healthcare challenge world. OA, a chronic condition characterized by inflammatory and degeneration, often present with joint pain and can lead to irreversible disability. While there is currently no cure for OA, it is commonly managed using nonsteroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, and glucosamine. Although these treatments can alleviate symptoms, it is difficult to effectively deliver and sustain therapeutic agents within joints. The emergence of nanotechnology, particularly in form of smart nanomedicine, has introduced innovative therapeutic approaches for OA treatment. Nanotherapeutic strategies offer promising advantages, including more precise targeting of affected areas, prolonged therapeutic effects, enhanced bioavailability, and reduced systemic toxicity compared to traditional treatments. While nanoparticles show potential as a viable delivery system for OA therapies based on encouraging lab-based and clinical trials results, there remails a considerable gap between current research and clinical application. This review highlights recent advances in nanotherapy for OA and explore future pathways to refine and optimize OA treatments strategies.